Regional Government Authority Model in Ecotourism Development in Baning Nature Park, Sintang District - Redin Redin (Sekolah Pascasarjana Universitas Brawijaya, 2020)
Management of Conservation Areas such as Taman Wista Alam, based on the Law on the Conservation of Living Natural Resources and Ecosystems and related regulations, often hinders the purpose of using TWA's main function to be developed as a natural tourism destination by local governments. The purpose of this research is to describe comprehensively and in detail the formulation of an alternative model of the authority of the Regional Government of Sintang District in the development of regional ecotourism in Baning Nature Tourism Park. This study uses an empirical legal study approach that relies on the data from interviews, observations, and documentation presented in a descriptive-analytical manner. The data analysis of this study used the Interactive Data Analysis model from Miles, Huberman, and Saldana. The results showed that the empirical model of the authority of the Sintang District government through the Tourism Office was limited to the management authority of areas outside the area, while within the area it was the authority of the Provincial BKSDA as the owner and manager of the area. To overcome the weaknesses of the empirical model, the advantages of the recommended model are needed, namely: (1) it can optimize synergy and collaboration in the management of ecotourism utilization blocks between the Sintang District Government and the West Kalimantan BKSDA; (2) the existence of a legal basis for management collaboration between the Sintang Regional Government and the West Kalimantan BKSDA to accelerate the development of supporting ecotourism infrastructure in the utilization block; and (3) empowering communities around the area.